2002
DOI: 10.2355/isijinternational.42.1033
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Crystallography of Intragranular Pearlite Transformation Nucleated at (MnS+VC) Complex Precipitates in Hypereutectoid Fe-Mn-C Alloys.

Abstract: Kinetics and crystallography of intragranular pearlite nucleated at the surface of (MnSϩVC) complex precipitate were studied in hypereutectoid Fe-Mn-C steels. The incoherent MnS embedded in the austenite does not act as a strong nucleation site of pearlite unless the transformation time is prolonged. The intragranular pearlite transformation is promoted effectively by the addition of vanadium (V). EPMA analysis showed that the intragranular pearlite nucleates on the (MnSϩVC) complex precipitate in the V-added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…They proposed that the non-equilibrium C-depleted zone around VC precipitated at the austenite grain boundary promotes the formation of such a ferrite in spite that the nominal composition should result in proeutectoid cementite precipitation. The present authors proposed a similar mechanism for the formation of intragranular pearlite on MnSϩVC complex precipitates in an Fe-Mn-C-V alloy, 8) of which composition is about the same as that of Han et al The complex transformation behavior with aging time at 1 173 K seen in Fig. 10 implies that non-equilibrium precipitation of V(C,N) affects strongly the kinetics of intragranular ferrite transformation as in the case of intragranular pearlite formation on the complex precipitate.…”
Section: Effect Of Inhomogeneous Distribution Of Alloyingmentioning
confidence: 88%
See 2 more Smart Citations
“…They proposed that the non-equilibrium C-depleted zone around VC precipitated at the austenite grain boundary promotes the formation of such a ferrite in spite that the nominal composition should result in proeutectoid cementite precipitation. The present authors proposed a similar mechanism for the formation of intragranular pearlite on MnSϩVC complex precipitates in an Fe-Mn-C-V alloy, 8) of which composition is about the same as that of Han et al The complex transformation behavior with aging time at 1 173 K seen in Fig. 10 implies that non-equilibrium precipitation of V(C,N) affects strongly the kinetics of intragranular ferrite transformation as in the case of intragranular pearlite formation on the complex precipitate.…”
Section: Effect Of Inhomogeneous Distribution Of Alloyingmentioning
confidence: 88%
“…Recently, some of the present authors reported an acceleration of pearlite transformation by the formation of MnSϩVC complex precipitates in Fe-12Mn-0.8C alloys with V addition. 8) However, there was no systematic study that examined the potency of inclusions as the nucleation site of ferrite in terms of the amount of MnS and V(C,N) during isothermal ferrite transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping combining SEI and EBSD has been successfully used for studying nucleation and growth of pearlite during pearlite transformation (Mangan & Shiflet, 1999;Guo et al, 2002;Kral & Spanos, 2003). It is accepted that surface contamination of the specimen after EBSD mapping can be removed after a very slight polish and the SEI images of the mapped region can be obtained through etching of the sample.…”
Section: Bsei Compared To Sei For Combining With Ebsdmentioning
confidence: 99%
“…The morphology of pearlitic structure can be determined by secondary electron imaging (SEI) in scanning electron microscope (SEM), whereas the crystallographic orientation of ferrite matrix (pearlite nodular) is generally determined by electron backscatter diffraction (EBSD). Combining SEI image and EBSD micrograph, both the morphology and crystallographic orientation of the pearlite can be revealed (Mangan & Shiflet, 1999;Guo et al, 2002;Kral & Spanos, 2003;Walentek et al, 2006). In the previous method, EBSD mapping was conducted firstly followed by etching of the specimen for acquisition of high-contrast SEI images.…”
Section: Introductionmentioning
confidence: 99%